Government Surveillance Accountability: The Failures of Contemporary Canadian Interception Reports - Molnar, Adam (2018)
Real time electronic government surveillance is recognized as amongst the most intrusive types of government activity upon private citizens’ lives. There are usually stringent warranting practices that must be met prior to law enforcement or security agencies engaging in such domestic surveillance. In Canada, federal and provincial governments must report annually on these practices when they are conducted by law enforcement or the Canadian Security Intelligence Service, disclosing how often such warrants are sought and granted, the types of crimes such surveillance is directed towards, and the efficacy of such surveillance in being used as evidence and securing convictions. This article draws on an empirical examination of federal and provincial electronic surveillance reports in Canada to examine the usefulness of Canadian governments’ annual electronic surveillance reports for legislators and external stakeholders alike to hold the government to account. It explores whether there are primary gaps in accountability, such as where there are no legislative requirements to produce records to legislators or external stakeholders. It also examines the extent to which secondary gaps exist, such as where there is a failure of legislative compliance or ambiguity related to that compliance. We find that extensive secondary gaps undermine legislators’ abilities to hold government to account and weaken capacities for external stakeholders to understand and demand justification for government surveillance activities. In particular, these gaps arise from the failure to annually table reports, in divergent formatting of reports between jurisdictions, and in the deficient narrative explanations accompanying the tabled electronic surveillance reports. The chronic nature of these gaps leads us to argue that there are policy failures emergent from the discretion granted to government Ministers and failures to deliberately establish conditions that would ensure governmental accountability. Unless these deficiencies are corrected, accountability reporting as a public policy instrument threatens to advance a veneer of political legitimacy at the expense of maintaining fulsome democratic safeguards to secure the freedoms associated with liberal democratic political systems. We ultimately make a series of policy proposals which, if adopted, should ensure that government accountability reporting is both substantial and effective as a policy instrument to monitor and review the efficacy of real-time electronic surveillance in Canada